2002
DOI: 10.1046/j.1471-6712.2002.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with illness‐related problems in persons with progressive muscular diseases: the Swedish version of the Ways of Coping Questionnaire

Abstract: One of the most widely used self-assessment inventories of coping is the Ways of Coping Questionnaire. The aims of the study were to describe coping with illness-related problems in persons with muscular diseases and to investigate the influence of demographic variables. Also, the reliability of the Swedish version of the Ways of Coping Questionnaire was to be evaluated. Forty-four persons with muscular dystrophy and 32 persons with postpolio syndrome, along with a comparison group of 214 students, completed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
0
20
1
Order By: Relevance
“…22 The WCQ has been widely used to explore parent coping. [23][24][25] Child Behavior Check List (CBCL), 26 a widely used tool, [27][28][29] measures parent perceptions of their child's problem behaviours. The CBCL consists of three categories of problems and a total score.…”
Section: Methodsmentioning
confidence: 99%
“…22 The WCQ has been widely used to explore parent coping. [23][24][25] Child Behavior Check List (CBCL), 26 a widely used tool, [27][28][29] measures parent perceptions of their child's problem behaviours. The CBCL consists of three categories of problems and a total score.…”
Section: Methodsmentioning
confidence: 99%
“…The scale has previously been translated into Swedish and used for Swedish patient populations [23]. Lundqvist and Ahlström [24] have confirmed that the Swedish version has satisfactory psychometric properties in clinical studies.…”
Section: Copingmentioning
confidence: 97%
“…The test consists of 66 items and the subjects are asked to rate their coping reactions, in relation to a stressful event, on a four-graded scale (0="does not apply/not used" to 3="used a great deal"). Acceptable internal consistency estimates for the eight clusters have been shown for the English version [27] and for the total score in a Swedish translation [28].…”
Section: Methodsmentioning
confidence: 89%